2019
DOI: 10.5125/jkaoms.2019.45.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral cleft lip: evaluation and comparison of treatment outcome with two surgical techniques based on qualitative (subject/guardian and professional) assessment

Abstract: Objectives The outcomes of the treatment of unilateral cleft lip can vary considerably due to variations in repair techniques. The aim of this study was to evaluate and compare treatment outcomes of surgical repair of unilateral cleft lip using either the Tennison–Randall or Millard technique based on (qualitative) parent/subject and professional assessments. Materials and Methods This was a prospective, randomized, controlled study conducted at Lagos University Teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
4
6
0
Order By: Relevance
“…This is also a statement by many surgeons worldwide. 9 , 10 In our study, the lip was too short in 34.8%, equivalent to that reported by Rajanikanth et al, but lower than that reported by Cheema SA and Asim M (63%). 6 , 7 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is also a statement by many surgeons worldwide. 9 , 10 In our study, the lip was too short in 34.8%, equivalent to that reported by Rajanikanth et al, but lower than that reported by Cheema SA and Asim M (63%). 6 , 7 …”
Section: Discussionsupporting
confidence: 74%
“…This is also a statement by many surgeons worldwide. 9,10 In our study, the lip was too short in 34.8%, equivalent to that reported by Rajanikanth et al, but lower than that reported by Cheema SA and Asim M (63%). 6,7 In patients with unilateral cleft lip, the short lip is often due to the selection of surgical methods that are not suitable for the type of cleft, such as the straight incision method or the rotation and advancement flap (incorrect rotation and advancement).…”
Section: Features Of Lip-skin Deformitysupporting
confidence: 64%
“…A linear cephalometric analytic obtained by projecting straight lines from the A and B points, respectively, unto the functional occlusal plane at 90 • and measuring the horizontal distance form point AO to BO direction of the jaw utterly influenced by the earlier treatment protocol such as time and techniques of primary surgeries (7)(8)(9)(10)(11)(12). The detrimental effect of palatoplasty on sagittal growth of maxilla has been widely documented in literature (9) but whether cheiloplasty impedes the growth is still in controversy (8,13). A number of researchers found that cheiloplasty has an effect on maxillary incisors, alveolar bone and development of maxilla as well whether some researchers claimed no effect on maxillary development (7,11,12,14,15).…”
Section: Wits Appraisalmentioning
confidence: 99%
“…Likewise, maxillary arch constriction (maxillary growth retardation) is a common dental problem of CLP patients, resulting in a concave facial profile ( Alam et al, 2019 ), class III malocclusion ( Alam et al, 2013 ), midfacial growth deficiency ( Alam et al, 2013 , 2019 ), and congenitally missing and malformed teeth. Orthodontic anomalies like crowding, rotation, and malposition of teeth are also commonly observed ( Haque and Alam, 2015a ; Haque et al, 2018 ; Adetayo et al, 2019 ). In the current study, maximum alterations in 8 different DC were found to be mostly altered in relation to upper incisors [U1-FH, U1-SN, U1-UOP, IIA, and U1-NA (degree)].…”
Section: Discussionmentioning
confidence: 99%